Analysis of Educational Policy Against Distance Learning During a Pandemic - Poniman Adyanto; Darno Darno; Muamar Al Qadri (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education policy is the subject of special attention by the government. This has become a matter of concern since the world was shocked by the outbreak of a virus called Corona or often referred to as Covid-19 (Corona Virus Diseases-19). This virus has led to the issuance of several government policies, especially in education, to prevent the spread of Covid-19. This study aims to analyze the educational policies that surround students in sustaining support in each of their learning processes so that the obstacles they face can be overcome through policies submitted by the government. This research uses a qualitative case study method through data sources taken from various relevant data sources, including journals and scientific papers on the case of the education policy raised, namely distance learning during the Covid-19 emergency. The study results indicate that the distance learning process currently being carried out cannot be called an ideal learning condition but an emergency condition that must be implemented. There are still various obstacles so that all learning can be optimal. The government is working with various related parties to make various efforts to overcome the problems that arise in distance gaining knowledge of, both in terms of regulations, increasing educator readiness, and expanding networks and get entry to studying sources, on the way to run effectively and efficiently